Adsorption of 4,4′-Dithiodipyridine Axially Coordinated to Iron(II) Phthalocyanine on Au(111) as a New Strategy for Oxygen Reduction Electrocatalysis - Herrera, Santiago Esteban (2018)
The coordination of PySSPy to FePc was monitored by UV/Vis spectroscopy while the adsobed FePc, anchored by PyS−Au(111), was examined by in situ STM in 0.1 M HClO4 and X-ray photoelectron spectroscopy (XPS). Rotating-disc-electrode (RDE) and linear-sweep-voltammetry (LSV) studies on the resulting FePc-modified Au(111) electrodes in an oxygen-saturated 0.1 M NaOH electrolyte exhibit excellent electrocatalytic properties for the oxygen reduction reaction (ORR), with a smaller overpotential than that observed for Au(111) with FePc deposited by direct adsorption from a benzene solution.